2012
DOI: 10.1080/17482798.2011.633406
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Media Exposure, Peers, and Family on Body Dissatisfaction amongst Boys and Girls in Singapore

Abstract: The role of media exposure, peers, and family on body dissatisfaction amongst boys and girls in Singapore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Although small negative correlations were found between time spent on YouTube, Instagram, and Snapchat and body satisfaction and a small positive correlation was found between time spent on YouTube and depressive symptoms, there were no unique associations between time spent on different platforms and mental health when controlling for the other social media activities, sex, and BMI. These results add to a growing body of research and debate within the literature (e.g., Cohen et al, 2017; Lwin & Malik, 2012; Meier & Gray, 2014; Orben & Przybylski, 2019; Twenge et al, 2017), suggesting that time spent on social media, regardless of the platform used, maybe less important for mental health than the activities users engage in on those platforms. This is perhaps not surprising given the diverse content available on social media and the ability of users to curate their social media environment.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although small negative correlations were found between time spent on YouTube, Instagram, and Snapchat and body satisfaction and a small positive correlation was found between time spent on YouTube and depressive symptoms, there were no unique associations between time spent on different platforms and mental health when controlling for the other social media activities, sex, and BMI. These results add to a growing body of research and debate within the literature (e.g., Cohen et al, 2017; Lwin & Malik, 2012; Meier & Gray, 2014; Orben & Przybylski, 2019; Twenge et al, 2017), suggesting that time spent on social media, regardless of the platform used, maybe less important for mental health than the activities users engage in on those platforms. This is perhaps not surprising given the diverse content available on social media and the ability of users to curate their social media environment.…”
Section: Discussionmentioning
confidence: 52%
“…Findings in this area are mixed and there are current debates between researchers regarding the importance and interpretation of the association between time spent on social media and adolescent mental health using large databases (Orben & Przybylski, 2019; Twenge, Joiner, Rogers, & Martin, 2017). Some studies have found that more time spent on social media is linked to more appearance concerns, eating disorder symptomology, social anxiety, and depressive symptoms among preadolescents (e.g., Fardouly, Magson et al, 2018; Tiggemann & Slater, 2014b; Tiggemann & Slater, 2015), adolescents (e.g., Tiggemann & Slater, 2014a; Twenge et al, 2017; de Vries, Peter, de Graaf, & Nikken, 2016), and young adults (e.g., Fardouly & Vartanian, 2015; Fardouly, Willburger, & Vartanian, 2018; Shaw, Timpano, Tran, & Joormann, 2015) while others have found no link between time spent on social media and those concerns and symptoms (e.g., Cohen et al, 2017; Lwin & Malik, 2012; Meier & Gray, 2014; Orben & Przybylski, 2019). The majority of research in this field has examined time spent on Facebook or Instagram.…”
Section: Introductionmentioning
confidence: 99%
“…After all, the media has established a clearer prescribed image of the societal ideal (thinness) for females as compared to males (McCabe & Ricciardelli, 2001), in which the perception of what the ideal male body is may not be uniform (Smolak & Murnen, 2008). Moreover, some have suggested that not all men define muscularity only as a physical attribute-some view non-physical attributes such as intelligence as the modern muscularity (Lwin & Malik, 2012). In addition to how social comparison with friends and celebrities relate to BID, DT, and DM among males and females, the gap between the mean scores of social comparison with friends and celebrities among men (comparison with friends: M = 2.67; comparison with celebrities: M = 2.35) was smaller than the differences for women (comparison with friends: M = 3.45; comparison with celebrities: M = 2.82).…”
Section: Discussionmentioning
confidence: 99%
“…After all, the media has established a clearer prescribed image of the societal ideal (thinness) for females as compared to males (McCabe & Ricciardelli, 2001), in which the perception of what the ideal male body is may not be uniform (Smolak & Murnen, 2008). Moreover, some have suggested that not all men define muscularity only as a physical attribute—some view non-physical attributes such as intelligence as the modern muscularity (Lwin & Malik, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation